Incredible story of social justice in India - Khanna, L. M. (New Delhi, 2002)
Despite a decade has passed since the Mandal judgement the problem of identification of other Backward Classes has not been solved. There are two aspects of the problem, a sociological aspects and a legal aspects. The legal aspects, again, has two components, determination in services and nature of backwardness. The first four chapters are description of sociological aspects with a view to find whether social perceptions of the latest operative judgement are based on social realities of Indian society. The next two chapters are an analysis of the judgment and whether the middle Classes were identified in accordance with the court's perceptions. Backward Classes Commissions appointed by the Central Government, intention of constituent Assembly in passing certain laws, some important judgments too are discussed. The final Chapter is about the Conundrum the nation still finds itself entangled.
Keywords: Social justice